Reduced longitudinal strain in the left ventricular inferior wall predicts malignant arrhythmia in non-ischemic heart failure. A DANISH substudy. (4th February 2022) - Winslow, UC; Thune, JJ; Elming, MB; Philbert, BT; Svendsen, JH; Pehrson, S; Jons, C; Bundgaard, H; Kober, L; Risum, N
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Small studies have suggested that poor regional myocardial function may be associated with malignant arrhythmias, in particular around the inferior-posterior region. We tested this hypothesis in a subgroup of patients from the DANISH trial. METHODS: From two centers, 317 patients with non-ischemic heart failure (LVEF < 35%) from the DANISH trial were evaluated by 2D-strain echocardiography. Regional strain was calculated as the average longitudinal strain in basal-, midventricular- and apical segments in each of the six left ventricular walls. Reduced regional function was defined as below-median regional strain. The endpoint was a composite of sudden cardiac death (SCD), sustained VT, admission with ventricular arrhythmia, and appropriate therapy from a primary prophylactic ICD. Time-to-first-event analysis was performed using Cox models. RESULTS: Mean age at inclusion was 62 years (72% male), median LVEF was 25% (IQR 20-30) median inferior strain was -8.7% (IQR -12.3; -4.9). After a five-year follow-up, 43 events were observed. Reduced inferior strain was associated with the composite endpoint in univariate analysis with a HR 2.08(95% CI 1.11-3.90), P = 0.021. After multivariate adjustment for clinical and echocardiographic parameters, inferior strain remained an independent predictor with a HR 2.78(95% CI 1.39–5.56), P = 0.004. Strain measurements in no other region were associated with the endpoint in the multivariate analysis. In subgroup analysis of patients in the two lower age tertiles (<68 of age) we found that reduced inferior- and posterior strain were associated with development of the composite endpoint after multivariate adjustment with HRs of 3.25(95% CI 1.41-7.53), P = 0.006 and 2.51(95% CI 1.14-5.53), P = 0.022. CONCLUSIONS: Low inferior-posterior strain was associated with a 2-3-fold increase in risk of malignant arrhythmia and SCD in patients with non-ischemic heart failure.